Influence of Oxygen Supply on Growth and Laccases Production by Pleurotus sajor-caju PS-2001 in Submerged Process - Bettin,Fernanda (2020)
Abstract (1) Background: Oxygen supply is an important parameter to be considered in submerged cultures. This study evaluated the influence of different conditions for dissolved oxygen (DO) concentration on laccases activities and growth of Pleurotus sajor-caju PS-2001 in submerged process in stirred-tank bioreactor. (2) Methods: Initially, three different conditions were tested: uncontrolled DO and minimum levels of 30% and 80% of saturation, with the pH controlled between 4.5 and 7.0. (3) Results: Best results were observed at 30% DO (26 U mL-1 of laccases at 96 h), whereas higher mycelial biomass was observed at 30% and 80% DO (above 4.5 g L-1). Four different conditions of DO (uncontrolled, 10%, 30% and 50% of saturation) were tested at pH 6.5, with higher laccases activity (80 U mL-1 at 66 h) and lower mycelial growth (1.36 g L-1 at 90 h) being achieved with DO of 30%. In this test, the highest values for volumetric productivity and specific yield factor were determined. Under the different pH conditions tested, the production of laccases is favoured at DO concentration of 30% of saturation, while superior DO levels favours fungal growth. (4) Conclusion: The results indicate that dissolved oxygen concentration is a critical factor for the culture of P. sajor-caju PS-2001 and has important effects not only on laccases production but also on fungal growth.